Aotearoa pioneering LGBTIQ, Indigenous and environmental production: The case of Rūrangi in New Zealand. Issue 2 (1st December 2021) - Molloy, Missy
This article spotlights the remarkable achievements of Rūrangi, a drama series and film created in Aotearoa New Zealand that breaks new ground in transgender production and representation. The case study mainly focuses on off-screen developments that shed light on Rūrangi's intersectionality, and on the compelling connections drawn by the creative team behind the project between trans identity and environmental and racial justice. Finally, the analysis touches on further innovations the Rūrangi team is implementing in its second season, which is currently in production.